Penciptaan Seni Lukis Semi-Realis Digital sebagai Apresiasi Terhadap Pemuda Penggiat Kebudayaaan Tradisional Masa Kini - Firstyan Artista Sakti; Triyono Widodo; Abdul Rahman Prasetyo (Graduate School of the Indonesia Institute of the Arts Yogyakarta, 2022)
Pola hidup pemuda penggiat kebudayaan tradisional yang dapat bersinergi dengan masa kini perlu diapresiasi dalam karya. Hal itu disebabkan oleh pemuda penggiat kebudayaan tradisional di masa kini menawarkan pola hidup yang dapat memanfaatkan kecanggihan zaman dan nilai luhur kebudayaan tradisional. Apresiasi dilakukan untuk menghargai pencapaian tersebut serta memberi wawasan tentang keberadaan pemuda penggiat kebudayaan tradisional kepada penikmat karya. Metode yang digunakan adalah empat tahap penciptaan milik Catharina Patrick. Tahapan tersebut antara lain, tahap persiapan, tahap penetasan, tahap inspirasi, dan tahap pengembangan. Seni lukis digital dengan corak semi realis dipilih sebagai bentuk perwujudan karya. Hasil dari keseluruhan proses penciptaan kali ini adalah enam karya lukis digital yang dicetak pada neon box. Digital Semi-Realist Painting Creation as an Appreciation for Youth Activists of Today's Traditional Culture Abstract The accomplished lifestyle of young traditional culture activists that could be synergized with the current situation should be appreciated through artwork. It was because the young traditional activists in the current situation offer a lifestyle that could optimize the recent development with the great value of traditional culture. The appreciation is created to value that achievement as well as give some insights about the existence of the young traditional culture activist to the artwork appreciator. The methodology used in this research is based on Catharina Patrick's four stages of creation, which were the preparation stage, idea emergence stage, inspiration stage, and development stage. The digital paintings with semi-realism visualization were selected as a medium for the artwork's embodiment. This creation process results are six digital paintings applied to neon boxes.